Large-Scale Structure of the Molecular Gas in Taurus Revealed by High Linear Dynamic Range Spectral Line Mapping - Goldsmith, Paul F; Heyer, Mark; Narayanan, Gopal; Snell, Ronald; Li, Di; Brunt, Chris (The Astrophysical journal, 2008)
We report the results of a 100 deg super(2) survey of the Taurus molecular cloud region in super(12)CO and super(13)CO [image]. The image of the cloud in each velocity channel includes [image] Nyquist-sampled pixels on a 20 super([image] ) grid. The high sensitivity and large spatial dynamic range of the maps reveal a very complex, highly structured cloud morphology, including filaments, cavities, and rings. The axes of the striations seen in the super(12)CO emission from relatively diffuse gas are aligned with the direction of the magnetic field. We have developed a statistical method for analyzing the pixels in which super(12)CO but not super(13)CO is detected, which allows us to determine the CO column in the diffuse portion of the cloud, as well as in the denser regions in which we detect both isotopologues. Using a column-density- dependent model for the CO fractional abundance, we derive the mass of the region mapped to be [image] M sub([image]), more than twice as large as would be obtained using a canonical fixed fractional abundance of super(13)CO, and a factor of 3 greater than would be obtained considering only the high column density regions. We determine that half the mass of the cloud is in regions having column density below [image] cm super(-2). The distribution of young stars in the region covered is highly nonuniform, with the probability of finding a star in a pixel with a specified column density rising sharply for [image] cm super(-2). We determine a relatively low star formation efficiency (mass of young stars/mass of molecular gas), between 0.3% and 1.2%, and an average star formation rate during the past 3 Myr of [image] stars yr super(-1).